Prevalence and antimicrobial resistance of salmonella isolates from chicken carcasses in retail markets in yangon, myanmar - Aung Zaw Moe (2018)
A cross-sectional investigation was conducted concerning prevalence, antimicrobial resistance, multidrug resistance patterns, and serovar diversity of Salmonella in chicken meat sold at retail in Yangon, Myanmar. The 141 chicken meat samples were collected at 141 retail markets in the Yangon Region, Myanmar, 1 November 2014 to 31 March 2015. Information on hygienic practices (potential risk factors) was retrieved via checklists. Salmonella was isolated and identified according to International Organization for Standardization methods (ISO 6579:2002) with minor modifications. Twelve antimicrobial agents belonging to eight pharmacological groups were used for antimicrobial susceptibility testing (disk diffusion method). Salmonella was recovered from 138 (97.9%) of the 141 samples. The isolates were most frequently resistant to trimethoprimsulfamethoxazole (70.3% of isolates), tetracycline (54.3%), streptomycin (49.3%), and ampicillin (47.1%). Resistance was also found to chloramphenicol (29.7%), amoxicillin-clavulanic acid (17.4%), ciprofloxacin (9.4%), tobramycin (8.7%), gentamicin (8%), cefazolin (7.2%), lincomycin-spectinomycin (5.8%), and norfloxacin (0.7%). Among the 138 Salmonella isolates, 72 (52.2%) were resistant to three or more antimicrobial agents. Twenty-four serovars were identified among the 138 Salmonellapositive samples; serovars Albany, Kentucky, Braenderup, and Indiana were found in 38, 11, 10, and 8% of samples, respectively. None of the potential risk factors were significantly related to Salmonella contamination of chicken carcasses. This study provides new information regarding prevalence and antimicrobial resistance and Salmonella serovar diversity in retail markets in Yangon, Myanmar.